Membangun Spiritualitas Bagi Warga Binaan di Lapas Melalui Pembinaan Rohani - Rugebregt, Irma (Sekolah Tinggi Teologi Simpson Ungaran, 2024)
Spiritual formation at the Saumlaki Class III Penitentiary, which is carried out through worship and other spiritual activities, is a form of application of Christian Religious Education to correctional inmates in increasing the spirituality of correctional inmates while they are serving a criminal term while in prison or when they have been released and living side by side. with the local community; therefore, this article discusses spiritual formation for correctional inmates by looking at the process and results of spiritual formation for inmates. This research was conducted at the Class III Saumlaki Correctional Institution. This research aims to explain the extent of the spiritual formation process and results for correctional inmates. The results of this research show that after the inmates undergo spiritual formation, the correctional inmates experience spiritual formation, which enables them to realize their mistakes, not repeat mistakes, accept themselves, and have a high motivation for life.